2021
DOI: 10.1111/1440-1703.12248
|View full text |Cite
|
Sign up to set email alerts
|

Dietary differences between grasshoppers are associated with life history tradeoffs in an alpine meadow

Abstract: Dietary differences are often observed among generalist herbivores co-occurring in the same community. However, the factors underlying the differences remain poorly understood. In the context of insect herbivores, we hypothesized that interspecific dietary differences are associated with life history traits. Specifically, we hypothesized that the size of wings as well as gender participate in defining dietary preferences, that is, long-winged species and males will tend to forage on plants with high C/N to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Fortunately, DNA metabarcoding provides an effective and accurate method for identifying the plant species (and their abundance) that are included in the diet of root feeders under natural conditions (Soininen et al, 2009). The reliability of this molecular method has been confirmed in the case of grasshoppers (Lan et al, 2021) and leaf roller beetles (Kajtoch et al, 2015). This study, as well as others, has shown that DNA metabarcoding can track feeding interactions that are not observable by means of traditional methods (Clare et al, 2014; Kress et al, 2015; Symondson, 2002; Valentini et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Fortunately, DNA metabarcoding provides an effective and accurate method for identifying the plant species (and their abundance) that are included in the diet of root feeders under natural conditions (Soininen et al, 2009). The reliability of this molecular method has been confirmed in the case of grasshoppers (Lan et al, 2021) and leaf roller beetles (Kajtoch et al, 2015). This study, as well as others, has shown that DNA metabarcoding can track feeding interactions that are not observable by means of traditional methods (Clare et al, 2014; Kress et al, 2015; Symondson, 2002; Valentini et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…The primers ITS2‐S2F and ITS2‐S3R (Chen et al, 2010) have been verified to quantify the intestinal plant species composition of grasshopper species by high‐throughput second‐generation sequencing (Lan et al, 2021), and the primers have a discriminatory power higher than that of plastid markers (Chen et al, 2010; Li, Gao, et al, 2011). In the case of root feeders, the DNA region used should be short enough to amplify degraded DNA (Staudacher et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional quality of food also plays an important role in mediating the flight-reproduction tradeoff because a high carbohydrate diet can eliminate the reproductive advantage of flightlessness in G. lineaticeps (Treidel et al 2021) while protein and carbohydrate effects on ovary versus flight muscle mass vary between flight-capable and -incapable G. firmus (Clark et al 2015). The nutrient content of food mediates life-history tradeoffs in other insects, as well (Gutiérrez et al 2020, Lan et al 2021) -thus, both food availability and quality may play important roles in driving plasticity in life-history strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the diversity of plant functional types (in the moderate grazing treatment) may facilitate the survival of generalist herbivore species requiring more than one functional type of plants [ 62 ]. For example, some grasshopper species are more generalized in feeding on both grass and forb species than some other grasshopper species [ 63 ]. In addition, grazing may directly facilitate herbivore species diversity.…”
Section: Discussionmentioning
confidence: 99%